Implementation of the Life Skills Curriculum in Shaping Students’ Character at De'green Camp High School, Tanjungpinang City - megawati, megawati (Jurnal Ilmiah Mandala Education (JIME), 2023)
Life skills are abilities that are driven by individuals to be willing and brave to face the problems of life and life normally without feeling forced, then proactively and imaginatively seek and explore the solutions obtained. De Green Camp Islamic School from the Tujuh Pilar Utama foundation has opened the Admission of New Learners (PPDB) for De Green Camp Islamic High School in 2022. A high school with the main goal of "skillful moslem". This research uses a descriptive qualitative approach of library research type, namely collecting data or scientific papers that aim as an object of research or data collection is literature. The results of the research found are, the Life Skills Curriculum offered by SMA Islam De Green Camp Kota Tanjungpinang is adjusted to the Vision and Mission that has been compiled by the foundation, life skills run by schools such as Literacy and life skills, self-actualization maps, and applied informatics. Various activities are carried out by adjusting the designed curriculum, so that teaching activities are in accordance with the curriculum in various other schools.